2018
DOI: 10.1016/j.athoracsur.2018.02.088
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Compared With Targeted Staging With Endobronchial Ultrasound in Patients With Lung Cancer

Abstract: In clinical practice, systematic sampling of the mediastinum by EBUS-TBNA, regardless of PET/CT features, is to be recommended over targeted sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…This has been shown for endobronchial ultrasound guided biopsy (EBUS-TBNA) for the staging of lung cancer. When comparing a systematic approach to a targeted, the former resulted in a higher diagnostic yield (30). Inspection of all segments is important as bronchoscopy can reveal endobronchial tumors that are not visible with computer tomography (31) and in patients not suspected for lung cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown for endobronchial ultrasound guided biopsy (EBUS-TBNA) for the staging of lung cancer. When comparing a systematic approach to a targeted, the former resulted in a higher diagnostic yield (30). Inspection of all segments is important as bronchoscopy can reveal endobronchial tumors that are not visible with computer tomography (31) and in patients not suspected for lung cancer (18).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with clinical N2 NSCLC, S anz- S antos et al . [11] reported that systematic EBUS-TBNA provided additional relevant staging information in 13% of cases. In a recent study by V ial et al .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in 93 patients reported on systematic nodal sampling in EBUS and concluded that routinely sampling more than two mediastinal stations may improve staging [24]. A recent single-centre retrospective study reported a 13% increase in important clinical information by systematic EBUS sampling compared to targeted EBUS [25]. We also found that systematic evaluation including routine sampling of (at least) stations 4R, 7 and 4L, if the short axis ⩾8 mm, increased sensitivity for nodal staging compared to PET-CT-guided targeted EBUS alone.…”
Section: Discussionmentioning
confidence: 99%